Analisis Penerimaan Learning Management System di Perguruan Tinggi Menggunakan Technology Acceptance Model (TAM) - Fitriadi Nurdin; Teguh Nur Santoso; Gamaruddin Gamaruddin (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to evaluate the utilization of the Learning Management System (LMS) by students of Universitas Terbuka (UT). The primary focus of this research is to comprehend the usage of LMS in higher education, with the research locations divided into three geographical zones: West (UT-Jakarta, UT-Surabaya, UT-Serang, UT-Pekanbaru, UT-Palembang, UT-Aceh), Central (UT-Pontianak, UT-Samarinda, UT-Makassar, UT-Kendari), and East (UT-Majene, UT-Mataram, UT-Palu, UT-Ternate, UT-Jayapura). The focus of the research is to identify factors influencing students not to participate in online classes, particularly related to the suboptimal utilization of the Online Tutorial service. In this study, 400 respondents were surveyed, all of whom are UT students. Data analysis was conducted using the SmartPLS application, utilizing the Technology Acceptance Model (TAM). The model involves both external variables and those within the TAM. The research findings indicate that the system quality significantly influences the use of LMS by students. Based on the gathered information, universities should enhance and regularly update features within the LMS to better support users efficiently.